CLASSROOM DEBATE STRATEGY TO ENHANCE STUDENTS’ CRITICAL THINKING SKILLS IN ARGUMENTATIVE WRITING - Naufal Fachrur Rozi (Universitas Muhammadiyah Makassar, 2021)
World’s massive agenda of promoting 21st century skills is a concrete truth that cannot be denied by everyone, including Indonesian students from all across range, In contrast, based on communal justification and researcher’s personal justification, the lack of Indonesian students’ critical thinking skills does exist. It is proven by Indonesia’s latest PISA score and researcher’s preliminary research at private university in Sidoarjo. In an attempt of overcoming the lack, this research aims to investigate the new paradigm that was rarely initiated to be conducted (i.e. enacting two mutually exclusive realms to be one unity), namely classroom debate to enhance students’ critical thinking skills in argumentative writing. This research employs descriptive qualitative research. The data were collected through observation and documentation from 19 undergraduate students who were currently mastering argumentative writing field of study at a private university in Sidoarjo. The obtained findings show that the assumption of the researcher in bringing up a new paradigm of classroom debate can enhance students’ critical thinking skills through argumentative writing is conceptually and practically correct. The result of three meetings of implementation and its seven main steps of implementation indicate that 19 research subjects’ critical thinking skills were progressively enhanced.